Assessing surface characteristics of eroded dentine with optical coherence tomography: a preliminary in vitro validation study - Habib, Madiha; Lee, Kuan Ming; Liew, Yih Miin; Zakian, Christian; Ung, Ngie Min; Chew, Hooi Pin (Optical Society of America, 2018)
We conducted the first pilot study to investigate the use of the attenuation coefficient from an optical coherence tomography (OCT) backscattered signal as a measure of surface roughness changes in eroded dentine at an early stage of the erosion process. Ten human premolar root samples were subjected to citric acid treatment before scanning by OCT. The extracted relative attenuation coefficient (μR) from backscattered OCT signals was shown to increase with the duration of acid challenge. Validated against roughness measurements (rSa) from scanning electron microscopy scans, μR is significantly correlated with rSa indicative of severity of erosion (p < 0.01, r = 0.9195). We conclude that the OCT attenuation coefficient of the immediate subsurface in eroded dentine is a potential surrogate measure for its surface roughness. However, further work should be performed to study how it relates to the surface and immediate subsurface changes effected by other mechanical wear before it could unequivocally be used as a surrogate measurement for surface roughness.